2020
DOI: 10.2169/internalmedicine.5000-20
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Medium- to Long-term Anti-TNF-α Antibody-based Maintenance Therapy in Behçet's Disease Patients with Intestinal Lesions

Abstract: Objective Anti-tumor necrosis factor (TNF)-α antibody-based regimens are effective in Behçet's disease (BD) with intestinal lesions. We therefore evaluated the efficacy of medium-to long-term anti-TNF-α antibody-based maintenance therapy of BD intestinal and non-intestinal lesions. Methods In this retrospective study, the response to the treatment was assessed endoscopically and clinically. Treatment responders were transferred to maintenance therapy. We evaluated the sustain rate of maintenance therapy, reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…9 Previous studies have shown that anti-TNF agents, including infliximab and adalimumab, led to the relief of gastrointestinal symptoms and ulcers in gastrointestinal tract in patients with Behcet's disease. [15][16][17][27][28][29][30][31][32][33][34][35][36] However, these studies were single-arm cohort studies. No randomized clinical trials have been conducted in this field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Previous studies have shown that anti-TNF agents, including infliximab and adalimumab, led to the relief of gastrointestinal symptoms and ulcers in gastrointestinal tract in patients with Behcet's disease. [15][16][17][27][28][29][30][31][32][33][34][35][36] However, these studies were single-arm cohort studies. No randomized clinical trials have been conducted in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal involvement was considered more dangerous to patients with Behcet's disease, as the prognosis was usually worse 9 . Previous studies have shown that anti‐TNF agents, including infliximab and adalimumab, led to the relief of gastrointestinal symptoms and ulcers in gastrointestinal tract in patients with Behcet's disease 15–17,27–36 . However, these studies were single‐arm cohort studies.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 12 included studies, 8 were retrospective studies and 4 were prospective studies. 21 , 22 , 26 34 Only one retrospective study made a comparison with the control group, 32 while the remaining 11 studies were single-arm type. The population of patients with ADA treatment reported by Inoue et al 21 was the same as that reported by Tanida et al ., 29 but the latter focused on a longer time.…”
Section: Resultsmentioning
confidence: 99%
“…Many reports confirmed the efficacy of anti-TNF-α antibody (infliximab/adalimumab) in the treatment of EB, where the remission rate can reach 80-89% [22][23][24]. There are also reports on the long-term efficacy of anti-TNF-α antibodies in treating EB [22]. Anti-TNF-α antibodies were also effective in preventing postoperative recurrence with a recurrence-free state for 2-3 years.…”
Section: Anti-tnf-alpha Agentsmentioning
confidence: 94%
“…Many reports confirmed the efficacy of anti-TNF-α antibody (infliximab/adalimumab) in the treatment of EB, where the remission rate can reach 80-89% [22][23][24]. There are also reports on the long-term efficacy of anti-TNF-α antibodies in treating EB [22].…”
Section: Anti-tnf-alpha Agentsmentioning
confidence: 95%